Experimental investigation on oxygenation efficiency of an effective aeration system for ponds - Kelestemur, Guluzar Tuna; Aytac, Ayca; Tuna, M. Cihat (Springer, 2024)
Dissolved oxygen (DO) concentration in water is one of the most important water quality parameters in rivers, lakes, and reservoirs. The most effective way to increase DO concentration in water is aeration. Conduits with high aeration performance are predicted to significantly increase aeration efficiency. Based on this prediction, the physical parameters affecting the aeration efficiency (E 20) of the conduit aeration system were experimentally investigated. The effect of different jet plunge angles, flow rates, hydrostatic levels, Froude numbers, and gate opening rates was investigated to optimize the system for the best ventilation efficiency. As a result, the aeration efficiency (E 20) improves with increasing air intake performance at low gate openings, high Froude numbers, and hydrostatic levels. The increase in jet plunge angles and hydrostatic level directly increases the aeration efficiency. The study showed that conduit systems can be an important alternative for pond aeration due to initial investment and operating costs, low energy cost, and high aeration efficiency.
Keywords: Aeration efficiency; Aquaculture; Pond aeration conduit